A hybrid system comprising an aerobic biological process and electrochemical oxidation for the treatment of black table olive processing wastewaters. (April 2016) - Tatoulis, Triantafyllos I.; Zapantiotis, Stamoulis; Frontistis, Zacharias; Akratos, Christos S.; Tekerlekopoulou, Athanasia G.; Pavlou, Stavros; Mantzavinos, Dionissios; Vayenas, Dimitrios V.
Abstract: In this work table olive processing wastewaters (TOPW) were treated by aerobic biological processes using indigenous microorganisms originating from TOPW, as well as the combination of two successive steps, i.e. aerobic biological treatment followed by electrochemical oxidation over a boron-doped diamond anode. In the single aerobic biological processes, experiments in suspended and attached growth reactors (trickling filters) were carried out using different TOPW feed concentrations of 5500 ± 350, 7500 ± 650 and 15, 000 ± 1050 mg dissolved COD L −1 . Two different operating modes were used to investigate the optimum performance of the filter, i.e. batch and SBR with recirculation. The latter mode with recirculation of 0.5 L min −1 led to high removal rates of dissolved COD and total phenolic compounds, up to 96.5% and 64.5%, respectively, for the initial COD concentration of 7500 mg dissolved COD L −1 . Depending on the type and operating conditions of the bioreactors, residual COD ranged between a few hundred and a few thousand mg L −1, while decolorization could not be achieved even under the most favorable conditions. A biologically treated effluent with residual dissolved COD of 5100 mg L −1 was completely mineralized and decolorized at 187.5 mA cm −2 applied current density; complete removal of COD, color and total phenolic compounds was achieved in 180–240 min, 30–60 min and 30 min of electrochemical oxidation, respectively. Lower treatment times and current densities were needed to polish effluents with lower organic loads. Highlights: Table olive processing wastewater (TOPW)was degraded by indigenous microorganisms. Suspended and attached growth reactors were examined forTOPW biodegradation. Removal rates of 96.5% dissolved COD and 64.5% phenolic compounds were recorded in the biofilters. Decolorization could not be achieved even under the most favorable conditions. Electrochemical oxidation-BDDdecolorized/mineralized the biologically treated TOPW.